ANALYSIS OF THE INFLUENCE OF PSYCHOGRAPHIC MARKET SEGMENTATION ON LOCAL RICE PURCHASE DECISIONS IN MODERN MARKET: A CASE STUDY OF CARREFOUR PENGAYOMAN MAKASSAR - Muslimah, Cantika Dara; Brasit, Nurdin; Hamid, Nurdjanah (The Scientia Journal of Financial issues, 2022)
The background of this research aims to understand the impact of market segmentation strategies on consumer purchasing decisions for local rice, which is typically bought in traditional markets but is now examined in modern markets. Companies need to know where they should target their market segmentation. Consumers have different ideas and thought patterns, and to continue meeting their needs, psychographic segmentation is necessary. The variables studied are psychographic variables and their influence on local rice purchase decisions in modern markets. To determine the extent of the influence of demographic market segmentation variables on purchasing decisions, this study uses a sample of 50 respondents who are local rice consumers at Carrefour Pengayoman Makassar Modern Market. The sampling method used is purposive sampling. The analysis technique used in this research is descriptive testing. The results show that psychographic market segmentation affects the purchasing decisions of local rice in modern markets.